Gene expression patterns and stress response in the copepod Calanus helgolandicus - Lauritano, Chiara; Cerra, Maria Carmela; Branno, Margherita; Ianora, Adrianna; Procaccini, Gabriele (My University, 2011)
Diatoms and dinoflagellates are dominant photosynthetic organisms in the world‟s oceans and are considered essential in the transfer of energy through marine food chains. However, these unicellular organisms produce secondary metabolites such as products deriving from the oxidation of fatty acids collectively termed oxylipins (including polyunsaturated aldehydes or PUAs; by diatoms) or potent neurotoxins (brevetoxins; by dinoflagellates). It is often assumed that harmful algae toxins are grazing deterrents to discourage zooplankton grazers from eating these algae. Some laboratory studies have suggested that some toxic algae are either not eaten by various grazers or that grazers ingesting toxic algae suffer adverse effects such as reduced feeding rates, diminished reproductive success, behavioral modification or increased mortality (Cohen et al., 2007, Kubanek et al., 2007; Prince et al., 2006). The aim of this thesis was to study in the copepod Calanus helgolandicus the effects of toxic diets at the molecular level. Expression level analyses by the sensible technique reverse transcription-quantitative polymerase chain reaction (RT-qPCR) allowed the study of specific genes of interest (GOI) which are known to have a primary role in generic stress responses, defense systems (e.g. aldehyde, free fatty acid and free radical detoxification) or apoptosis regulation in other organisms, from humans to marine organisms (Bouraoui, et al., 2009; Einsporn, et al., 2009; Hasselberg, et al., 2004; Kim, et al., 2008; Olsvik, et al., 2009; Salazar-Medina, et al., 2010; Snyder, 2000; Vasiliou, et al., 2004; Wan, et al., 2011). The GOI analyzed were two heat shock proteins (HSP70 and HSP40), six Aldehyde dehydrogenases (ALDH2, ALDH3, ALDH6, ALDH7, ALDH8, ALDH9), Cytochrome P450-4 (CYP4), Catalase (CAT), Superoxide Dismutase (SOD), Glutathione S-Transferase (GST), Glutathione Synthase (GSH-S), Inhibitor of Apoptosis Protein (IAP), Cell Cycle and Apoptosis Regulatory 1Protein (CARP), Cellular Apoptosis Susceptibility Protein (CAS), actin (ACT) and Alpha and Beta tubulins (ATUB and BTUB). These GOI were analyzed in various experimental conditions: copepods exposed to algae which produce or do not produce toxic metabolites, including dinoflagellates (Prorocentrum minimum, Rhodomonas baltica or Karenia brevis) and diatoms (Chaetoceros socialis and Skeletonema marinoi), during field or laboratory experiments. In addition, the effect of the oxylipin producing diatom Skeletonema marinoi has been tested on two different C. helgolandicus populations: the Mediterranean population collected in the Adriatic Sea and the Atlantic population collected in the English Channel. According to the results obtained, expression levels of the specific GOI changed depending on the tested algae, times of exposure, copepod population analyzed and field/laboratory experiments. Gene expression level patterns in the different experimental conditions tested may help to understand the copepod response to stressful conditions. The identification of new genes, for example using cDNA libraries or new generation sequencing, and the application of new tools, such as functional proteomic approaches, may allow for a more comprehensive overview of how copepods respond to specific stressors in the laboratory, but also to predict the response under natural environmental conditions and the effects of these responses on higher trophic levels.
Dottorato di Ricerca in Biologia Animale, XXIV Ciclo, a.a.2010-2011
Keywords: Biologia; Fisiologia animale; Diatomee; Copepodi